FORMATION OF READINESS OF FUTURE TEACHERS FOR THE ORGANIZATION OF PARTNERSHIP INTERACTION BETWEEN PARTICIPANTS OF THE EDUCATIONAL PROCESS - Natalia Golota; Antonina Karnaukhova (Borys Grinchenko Kyiv Metropolitan University, 2020)
In the article the peculiarities of forming of future teachers' readiness for the organization of pedagogical partnership in pre-school educational establishments and elementary schools are revealed. Psychological and pedagogical researches concerning scientific interpretations of the concept of readiness in future teachers for professional activity are analyzed. The basic technologies and methods, which are used to form readiness of future teachers to organize pedagogical partnership in the teaching of pedagogical disciplines, are explained. The features of application of different technologies (situational modeling, dialog, personal oriented, communicative) and methods (research tasks, thematic projects aimed at solving educational problems on different sociocultural topics (problems), which have shown their effectiveness in forming readiness to form readiness, are characterized to a pedagogical partnership. In the course of studying the content module «Pedagogical Partnership» of the integrated course «Pedagogy» for students of 1-2 year of specialty «Preschool education» and discipline «Didactics of elementary school» for students of 1-3 course of specialty «Elementary education», that the pedagogical partnership not only contributes to the creation of an effective educational space for preschool education and general secondary education, while ensuring unity in the education and training of preschool and primary school children, but also psychologists but comfortable conditions for each participant of the educational process is an important mechanism for quality assurance. Based on the results of the study, the essence of the concept of «future teachers' readiness for the organization of pedagogical partnership in educational institutions» is defined as an integral formation, which includes the ability to communicate with the participants of the educational process, willingness to interact, design a model of optimal behavior in different situations and situations as subjects of educational activity, and various social institutions for the sake of full, comfortable stay of the child in educational essays.